Helen Ahpornsiri's Beneath the waves - Murray, Lily (Big Picture Press, 2019)
Take a journey through the oceans of the world in this beautiful book, made entirely from hand-pressed plants. Artist Helen Ahpornsiri transforms silky seaweeds, feathery algae and bright coastal blooms into playful penguins, scuttling crabs and schools of silvery sharks. Turn the page to explore each corner of the oceans, from hidden rock pools to the darkest depths. Marvel as plants transform into marvellous creatures, and discover the magic and beauty that lies beneath the waves